Mathematical Modelling of Syphilis Transmission Dynamics: Impacts of Mass Media Report, Risky Sexual Behavior and Treatment - Mwanga, Gasper G. (Tanzania Journal of Science, 2022)
Syphilis is one of the deadly sexually-transmitted diseases. This paper studied the impacts of sexual behavior, mass media report and treatment of infected individuals on the dynamics of syphilis transmission. The analytical and numerical analyses of the model are presented. The disease free equilibrium of the model is both locally and globally asymptotic stable when the associated reproduction number is less than unity. Analysis of the Reproduction number shows that it is not possible to control syphilis disease transmission if the rate of individuals practicing risky sexual behavior is high. Furthermore, the treatment of late (latent and tertiary) syphilis infection is beneficial to the infected individuals, but has no impact in the lowering of the reproduction number. This study suggests that the effective control strategy of syphilis must focus on lowering the number of individuals practicing risky sexual behavior and applying higher treatment rates for early syphilis infections. Furthermore, the media function should address the issues regarding safe sexual behavior. Keywords: Syphilis, sexually transmitted infection, Risky sexual behavior, Mass media